Role of IL-1 receptor-associated kinase-M (IRAK-M) in priming of immune and inflammatory responses by nitrogen bisphosphonates - Norton, John T. (National Academy of Sciences, 2011)
Nitrogen bisphosphonates (NBPs) are commonly prescribed for osteoporosis but have also been found to induce inflammatory reactions and to delay the progression of breast cancer. The inflammatory and anticancer effects of the NBPs might be associated with an ability to modulate innate immune signaling. In mice, intraperitoneal NBP administration causes a rapid influx of neutrophils and monocytes that is dependent on the myeloid differentiation primary response gene 88 (MyD88) mediator of Toll-like receptor (TLR) and IL-1 signaling. Bone marrow chimeras demonstrate that this inflammatory response is partially dependent on TLR4 expression by hematopoietic cells and the IL-1 receptor on radioresistant cells. In vitro, NBPs directly stimulate neither murine bone marrow-derived mononuclear cells nor human peripheral blood mononuclear cells, but rather prime them to produce increased amounts of cytokines when exposed to IL-1 or TLR ligands. This potentiation is mediated by a reduction in IL-1 receptor-associated kinase-M, a negative regulator of MyD88-dependent signaling. In vivo, this property renders the NBPs as effective adjuvants that enhance both cellular and antibody responses to antigens.